2018
DOI: 10.7196/sajog.1226
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the indications for caesarean sections at Chris Hani Baragwanath Academic Hospital

Abstract: RESEARCH Background.A systematic review concluded that a caesarean section (CS) performed for medical indications will save lives; however, it is associated with short-and long-term complications. The CS rate at Chris Hani Baragwanath Academic Hospital (CHBAH) was 39.78% in 2015. Objectives. To evaluate the indications for CSs at CHBAH. Methods. This was a cross-sectional study conducted on the data collected in the week of 23 June to 29 June 2015. Each file was evaluated for the correctness of the decision by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
2
4
0
Order By: Relevance
“…29,30 Also, interobserver interpretation of foetal heart rate for diagnosis of foetal distress has been shown to be only moderate 31 and when no specific standard guideline is followed to diagnose foetal distress, studies have shown that the sensitivity and specificity of CTG were also affected. 32,33 Our findings show an increase in foetal distress compared to a previous study in 2015 by Adam et al 34 at CHBAH, which found that foetal distress (49.7%) was the most common indication for caesarean delivery followed by dystocia and previous caesarean delivery. These findings are consistent with a study by Mittal et al, 35 which showed that foetal distress as an indication for emergency delivery was increasing annually.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…29,30 Also, interobserver interpretation of foetal heart rate for diagnosis of foetal distress has been shown to be only moderate 31 and when no specific standard guideline is followed to diagnose foetal distress, studies have shown that the sensitivity and specificity of CTG were also affected. 32,33 Our findings show an increase in foetal distress compared to a previous study in 2015 by Adam et al 34 at CHBAH, which found that foetal distress (49.7%) was the most common indication for caesarean delivery followed by dystocia and previous caesarean delivery. These findings are consistent with a study by Mittal et al, 35 which showed that foetal distress as an indication for emergency delivery was increasing annually.…”
Section: Discussionsupporting
confidence: 54%
“…Our findings show an increase in foetal distress compared to a previous study in 2015 by Adam et al 34 at CHBAH, which found that foetal distress (49.7%) was the most common indication for caesarean delivery followed by dystocia and previous caesarean delivery. These findings are consistent with a study by Mittal et al, 35 which showed that foetal distress as an indication for emergency delivery was increasing annually.…”
Section: Discussionsupporting
confidence: 49%
“…Improving hospital guidelines or training on interpretation of cardiotocographs may help to reduce CS for fetal distress. [17] Increased use of TOLAC could possibly help in reducing the size of group 5, as mentioned previously. Together, groups 6 and 7 contributed 4.7% to the overall CS rate.…”
Section: Discussionmentioning
confidence: 92%
“…A retrospective study conducted over 1 week at CHBAH in 2015 found that 8.16% of women who underwent CS had PPH, which is very similar to our rate of 8.3%. [17] To compare this with high-income countries, the International Postpartum Haemorrhage and Collaborative Group illustrated an increasing trend in PPH in immediate/atonic PPH in Australia, Canada and the USA, but this still only accounted for <7% of deliveries in all three countries in 2006. [18] Our high rates of PPH at CS may be related to our ratio of emergency to elective CS, our large numbers of CSes for previous CS, which are often more difficult surgeries, and the relative skill or seniority of the surgeon and anaesthetist attending the CS.…”
Section: Discussionmentioning
confidence: 99%
“…17 However, macrosomia, PNM, and prematurity remain inferior to respective rates in South Africa for non-diabetic pregnancies. [18][19][20][21][22] The rate of cesarean delivery (n=641, 72.2%) was much higher in the present study than the estimated rate of cesarean delivery at CHBAH of 39.8% in non-diabetic pregnancies, 23 but only T A B L E 3 Comparison of baseline characteristics in metformin monotherapy and glibenclamide-exposed groups vs insulin monotherapy. moderately higher than the 1992-2002 audit of diabetic pregnancies (62%), a difference that could be due to an overall increase in rates of cesarean delivery over this period.…”
Section: Discussionmentioning
confidence: 89%